The un-veiling of Alice in O fotógrafo e a rapariga, by Mário Cláudio - Dottling Dias, Gabriel (2022)
This paper intends to provide a critical reading of the novel O Fotógrafo e a Rapariga (2015), by Portuguese author Mário Claudio, considering the building of the character Alice Liddell through procedures that involve the memory – which allows (re)writing the character’s own story within the novel. For that, it will be necessary to scrutinize the elaborated narrative and intertextual game that pervades the novel. In order to analyze the writing of the character, we are going to rely on her memories, her daydreaming thoughts, the stories she tells and the photos taken by Charles Dodgson. From this sophisticated textual game, we will un-veil Alice with the purpose of understanding the how the book unfolds.